Effect of pH on Toxicity of Zinc Sulphate Hydrate Solutions Using the Spirotox Test - Hoang, Quynh Thi Ngoc; Petrov, Gleb Vladimirovich; Koldina, Alena; Syroeshkin, Anton (Journal of Drug Delivery and Therapeutics, 2024)
Introduction: Spirostomum ambiguum is commonly used as a biological indicator due to its high sensitivity to heavy metals. It functions normally across a wide pH range of 4.5 to 8.0. Testing on protozoan organisms provides a general understanding of the impact of pH on the toxicity of zinc in pharmaceuticals. By investigating the toxicity of zinc in environment with varying pH levels, the optimal environment for zinc absorption can be determined. Objective: The objective of this study is to assess the toxicity of zinc sulphate solutions using different forms of hydrating and at various pH levels, applying the Spirotox method. Methods: An experiment was conducted using a solution of pharmaceutical substances, specifically zinc sulphate heptahydrate and zinc sulphate monohydrate, with a concentration of 0.01 M. The study aimed to investigate the effect of the solution on the lifespan of S.ambiguum within the pH range of 4.8-6.5. Results: Arrhenius activation energy (Ea linear correlates with LD50 oral toxicity for rats) decreases as pH increases from 4.8 to 6.5 for ⋅7 and ⋅ solutions. The values decrease from 140±10 kJ/mol to 55±10 kJ/mol and from 110±2 kJ/mol to 60±10 kJ/mol, respectively. Conclusion: It was found that the toxicity of zinc sulphate hydrate solution towards S. ambiguum increased as the pH value increased. Hydrating of the active pharmaceutical substance was a crucial factor, it is critically important for preparation of solutions of an active pharmaceutical substance. Keywords: zinc sulphate, Spirotox test, pH, activation energy, toxicity.